2021
DOI: 10.1111/ajt.16197
|View full text |Cite
|
Sign up to set email alerts
|

Acute murine cytomegalovirus disrupts established transplantation tolerance and causes recipient allo-sensitization

Abstract: We have previously shown that acute cytomegalovirus (CMV) infection disrupts the induction of transplantation tolerance. However, what impact acute CMV infection would have on the maintenance of established tolerance and on subsequent recipient allo‐sensitization is a clinically important unanswered question. Here we used an allogeneic murine islet transplantation tolerance model to examine the impact of acute CMV infection on: (a) disruption of established transplantation tolerance during tolerance maintenanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…49 Importantly, it does appear that apoptotic donor cellinduced tolerance can be disrupted in the experimental setting by specific immunological challenges. Cytomegalovirus infection breaks established tolerance in a model of murine islet allotransplantation, 81 a mechanism that appears dependent on the conversion of anergic T cells to IFN-γproducing effector T cells. 82 Other similar models of tolerance using donor-specific transfusion have shown that disruption of tolerance also occurs with Toll-like receptor engagement after CpG (5-cytosine-phosphate-guanine-3) oligonucleotide administration.…”
Section: Efficacy Of Apoptotic Donor Cells In Animal Modelsmentioning
confidence: 99%
“…49 Importantly, it does appear that apoptotic donor cellinduced tolerance can be disrupted in the experimental setting by specific immunological challenges. Cytomegalovirus infection breaks established tolerance in a model of murine islet allotransplantation, 81 a mechanism that appears dependent on the conversion of anergic T cells to IFN-γproducing effector T cells. 82 Other similar models of tolerance using donor-specific transfusion have shown that disruption of tolerance also occurs with Toll-like receptor engagement after CpG (5-cytosine-phosphate-guanine-3) oligonucleotide administration.…”
Section: Efficacy Of Apoptotic Donor Cells In Animal Modelsmentioning
confidence: 99%
“…Our lab has demonstrated in a murine islet transplant model that acute murine-CMV(MCMV) infection alters MDSC differentiation, promoting maturation of immature myeloid cells to become inflammatory monocytes which subsequently prime alloreactive CD8 T cells that prevent the induction of tolerance ( 78 ). In mice where MCMV infection was introduced days after donor ECDI-SP infusions, it not only led to the disruption of tolerance otherwise induced by donor ECDI-SP infusions, but also resulted in accelerated rejection of a subsequent same-donor islet transplant as a consequence of anti-donor memory T cell response ( 118 ).…”
Section: Limitationsmentioning
confidence: 99%
“…We next perturbed this stable tolerance on day 95 after transplantation by giving acute murine cytomegalovirus (MCMV) infection to tolerized mice, which has been previously shown to precipitate allograft rejection in approximately 60%–70% recipients over the ensuing 5–6 weeks ( 5 ). Interestingly, at the time of rejection, we observed a significant reduction of the number of intragraft CD73 hi FR4 hi T AN cells, along with a significantly reduced level of CD73 and FR4 expression on remaining T AN cells ( Figure 1B ).…”
mentioning
confidence: 99%